Occult hemoptysis: a rare case of esthesioneuroblastoma - Jain, Shalini; Sen, Kanwer (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Esthesioneuroblastoma forms a part of the spectrum of rare malignancies of the olfactory neuroepitheliem. The rarity of the tumour precludes systematic approach to clinical diagnosis and management. This study involves a case of 68 years old female who presents with chief complaints of hemoptysis for 3 months in the medical outpatient department with no nasal signs and symptoms. After referral to chest physician she is referred for ear nose and throat opinion. Esthesioneuroblastoma presentation is very varied and the case reports published have been very few. In view of the rarity of the tumour, clinical suspicion is essential in unusual presentation of hemoptysis.